THE USE OF CODE-SWITCHING AND CODE-MIXING IN PUBLIC SPEAKING CLASS AT HIGHER EDUCATION ISLAMIC - Sulianur Sulianur; Imam Qalyubi; Sabarun Sabarun (IKIP Siliwangi, 2022)
This study attempted to find out how students view the use of code switching and code mixing when learning in public speaking course. Code switching is the switching of two languages from one language to another or language variations in one conversation across sentence or clause boundaries. While code mixing is one language to another in the same speech or in the same spoken or written text. This study used 15 class A students of 2020 and a lecturer who taught public speaking courses in that class. This research used a case study method, while the instruments used were observation, interviews, and documentation. The results of the study were (1) code switching and code mixing was very influential in learning especially public speaking. These codes were very helpful in understanding English fully, so that there was no misunderstanding in receiving material from the lecturer, and so that the learning process can run well and the learning materials can be accepted by students perfectly. (2) Several factors caused code switching and code mixing to be carried out in public speaking class, the factors were: (a) Avoid misunderstanding when delivering material. (b) To make sure the student understood what he talked about. (c) To make the learning process be easier, make students able to receive learning materials well. (3) Based on observation, interview, and data documentation, the finding revealed that code switching and code mixing happened when was absent and during learning, the types used by lecturer only code switching, they called as intra sentential, inter sentential, and emblematic. Keywords: Code Switching, Code Mixing, Public Speaking